PENINGKATAN KEMAMPUAN PEMAHAMAN MATEMATIS PESERTA DIDIK MENGGUNAKAN MEDIA VIDEO PEMBELAJARAN PASCA COVID-19 - Nurshifa Nurshifa; Dwi Desmayanasari; Noprisa Noprisa; Fitria Lestari (Hipotenusa Journal of Research Mathematics Education (HJRME), 2022)
This study aims to determine the improvement of students' mathematical understanding skills using instructional video media. This research was conducted at one SMP Negeri 3 Tanjung Bintang, South Lampung 2021/2022. The subjects in this study were students of class VIII consisting of an experimental class and a control class, each of which was opened by 30 students. The samples were taken in this study using a purposive sampling technique. Data collection in the form of pretest and posttest. Pretest and posttest were used to measure mathematical understanding ability. The results showed an increase in the mathematical understanding of the experimental class 81,187 and the control class 71,349 t test resulted in a value of sig (2-tailed ) = 0.000 < 0.05 then H0 was rejected so that the average score for increasing the understanding of mathematical concepts in the experimental class was better than the average score. control class improvement.